Manajemen Dana Bantuan Operasional Sekolah untuk Pencapaian Mutu Pembelajaran - Siti Badriah; K.A Rahman; muazza . (Universitas Pendidikan Indonesia, 2022)
This research aims to show how the management of School Operational Assistance (BOS) funds is implemented to achieve learning quality. This research uses descriptive method with qualitative approaches in Junior high school in Muaro Jambi. The results showed: (1) The implementation of the management of BOS funds at junior high schools in Muaro Jambi has been based on applicable laws and technical guidelines. But the result is not optimal because of the limited funds received by the school; 2) In reality the principal difficult to use the funds exactly in accordance with RKAS. The school principal also difficult to innovate because the use of the funds should not be used instead of the 13 components that have been specified in the Technical Handbook (Technical Guidance) use of the funds. 3) Delays in the distribution of BOS funds be an obstacle big enough and the lack of awareness and understanding of the principals in managing the BOS funds are transparent and accountable. This makes is difficult to increase the quality of education; and 4) The biggest allocation is to meet the standards development costs educators as well as the process of teaching and learning activities.